A mass transfer correlation for packed bed of lead oxide spheres in flowing lead–bismuth eutectic at high Péclet numbers. (January 2015) - Marino, A.; Lim, J.; Keijers, S.; Vanmaercke, S.; Aerts, A.; Rosseel, K.; Deconinck, J.; Van den Bosch, J.
Abstract: It is widely recognized that the control of the activity of dissolved oxygen is essential for the use of lead–bismuth eutectic (LBE) as primary coolant for nuclear systems. A lead oxide mass exchanger (PbO MX) comprised of a packed bed of lead oxide spheres is a promising solution to regulate the dissolved oxygen activity in the LBE. In order to design and operate a PbO MX properly, the dissolution kinetics of PbO in flowing LBE should be determined. A high-fidelity Computational Fluid Dynamic (CFD) model of solid-to-liquid mass transfer has been developed to determine the mass transfer coefficient of a PbO MX in flowing LBE. We validated the developed CFD model against experimental data obtained from the LBE test loop CRAFT, at SCKCEN. The model is in good agreement with the experimental data. The effect of the channel to particle diameter ratio ( R ) on the mass transfer coefficient was evaluated by using the validated model. A mass transfer correlation for PbO MX was obtained, in terms of the Sherwood number, by fitting the simulation results for the general case of a random packed bed with a porosity of about 0.4.